The Difference between Leasing, Loans and Financing Referring to the Law and Regulations - Suwinto Johan (Simbur Cahaya, 2023)
The terms leasing, financing and lending are often misused because people often think that all three terms mean the same thing. In fact, these terms are different schemes and roles based on applicable laws. Each financing has a different purpose of use. This normative juridical study discusses the differences between leasing, financing and loans or credit based on the applicable laws and regulations. This study uses library research and related laws and regulations. The results of this study indicate that there are significant differences between leasing, financing and loan schemes. Leasing for productive business activities and financing for consumptive activities, while credit is for all segments. Leasing is used to purchase productive goods and consumer financing to purchase consumer goods. The three types of financing are provided by financial institutions. Leasing and financing is provided by finance companies. Loans are provided by banks. Each scheme targets a different customer market and has different advantages and disadvantages for providers and customers. Leasing provides advantages in terms of taxation compared to other financing. In addition, property rights also differ between leasing, financing and loans. Agreements with collateral for goods are adjusted to the type of financing that also differs from one financing to another. Further research can be carried out by conducting empirical research through field surveys to focus group discussions. With a focus group discussion, the opinions of business actors can be concluded in the joint discussion. Thus, the research results will complement existing research